Awareness of Liver Cancer among Adult Population of Selected Community of Gorkha District: A Cross-Sectional Study - Panthee, Sabita; Rana, Sapana; Upadhayay, Hari Prasad (Journal of Bharatpur Hospital, 2026)
Background Cancer is an abnormal uncontrolled cells growth with ability to infiltrate and destroy normal tissues. Liver cancer is a major public health concern with increasing incidence and mortality worldwide. Awareness and early recognition of risk factors and symptoms play a crucial role in prevention and timely treatment. In Nepal, limited community-level data exist regarding public knowledge of liver cancer. Understanding current awareness levels can help guide targeted health education and prevention strategies. Methods A descriptive cross-sectional research study was conducted at Ahale 8, Gorkha to identify the awareness regarding Liver Cancer among community people from 18 to 31 May, 2025.There were 116 samples were included by using non-probability purposive sampling technique. Data was collected by structured interview schedule, analyzed in SPSS version 22 and interpreted by using descriptive and inferential statistics. Results The study showed mean age of respondent as 41.28± 10.233, 60.3% of respondent were female, 56.0% were Janajati and majority 92.2% were Hindu. The 40.5% respondents completed secondary level education and 54.3% respondents income was sufficient for below than 3 months. The level of awareness among respondents had 86.3% poor, 10.3% moderate & 2.6% good. There were statically significant with gender, income and family history of liver cancer at p-value <0.005. Conclusions This study concludes that there is poor level of awareness among community people which indicate a need for awareness program on liver cancer and measures to be followed for the prevention and screening in general people.